1995
DOI: 10.1074/jbc.270.45.26923
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Soluble Epoxide Hydrolase

Abstract: 18O-Labeled epoxides of trans-1,3-diphenylpropene oxide (tDPPO) and cis-9,10-epoxystearic acid were synthesized and used to determine the regioselectivity of sEH. The nucleophilic nature of sEH catalysis was demonstrated by comparing the enzymatic and nonenzymatic hydrolysis products of tDPPO. The results from single turnover experiments with greater or equal molar equivalents of sEH:substrate were consistent with the existence of a stable intermediate formed by a nucleophilic amino acid attacking the epoxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
47
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(54 citation statements)
references
References 36 publications
7
47
0
Order By: Relevance
“…Both mutations of the two tyrosines increased IC 50 values for ureas tested (Table III). Because the epoxide substrates are susceptible to an S N 2 backside attack on the carbon of epoxide ring by nucleophilic Asp 333 (13), the angle and distance of these two tyrosines are suitable to activate epoxide oxygen in concert with nucleophilic attack by Asp Tyr 381 , and the substrate epoxide oxygen modeled into the sEH active site (26) is quite consistent with the preferred stereochemistry of such interactions reflected by the examples from the Cambridge Structural Data base. Epoxide-phenol hydrogen bond stereochemistry is also consistent with the preferred stereochemistry of hydrogen bonds to tyrosines in refined protein structures as outlined by Ippolito et al (39).…”
Section: Inhibition Of Tyrosine Mutants By Ureas and Carbamate-supporting
confidence: 52%
See 1 more Smart Citation
“…Both mutations of the two tyrosines increased IC 50 values for ureas tested (Table III). Because the epoxide substrates are susceptible to an S N 2 backside attack on the carbon of epoxide ring by nucleophilic Asp 333 (13), the angle and distance of these two tyrosines are suitable to activate epoxide oxygen in concert with nucleophilic attack by Asp Tyr 381 , and the substrate epoxide oxygen modeled into the sEH active site (26) is quite consistent with the preferred stereochemistry of such interactions reflected by the examples from the Cambridge Structural Data base. Epoxide-phenol hydrogen bond stereochemistry is also consistent with the preferred stereochemistry of hydrogen bonds to tyrosines in refined protein structures as outlined by Ippolito et al (39).…”
Section: Inhibition Of Tyrosine Mutants By Ureas and Carbamate-supporting
confidence: 52%
“…1) (6). The mechanism of murine sEH has been mainly elucidated from a series of experiments utilizing heavy isotopes, protein mass spectrometry, and sitedirected mutagenesis (12,13). They indicated that Asp 333 acts as a catalytic nucleophile and that a water molecule is activated by the nearby His 523 and Asp 495 pair (Fig.…”
mentioning
confidence: 99%
“…Although heterogeneous, this group of enzymes share features regarding overall structural fold as well as activesite architecture [20]. The enzyme active site contains a proteinderived nucleophilic group (aspartic acid) that has been shown in mammalian epoxide hydrolases to attack an electrophilic carbon of the bound substrate to form an alkylated enzyme intermediate [21,22]. A nearby acid (tyrosine phenol) facilitates ring opening of the oxirane oxygen [12,14].…”
Section: Introductionmentioning
confidence: 99%
“…The C-terminal domain, or "catalytic domain," contains the active site residues required for epoxide hydrolysis. By analogy with related ␣/␤ hydrolases such as haloalkane dehalogenase (11)(12)(13) and in accord with labeling (14) and site-directed mutagenesis experiments (15,16) , and a hydrogen bond may form between these two residues during catalysis. Given its active site location and absolute conservation among all sequenced epoxide hydrolases, Tyr 465 is a likely general acid that donates a proton to the epoxide oxygen in the first step of catalysis (8,17).…”
mentioning
confidence: 99%